Happily ever after? Socioeconomic profiles in divorce cases during the first half of the 20th century, Buenos Aires province, Argentina - Valobra, Adriana (2021)
Absolute divorce in Latin America has been studied, in particular, concerning those countries where its legal sanction was given early . However, not long ago, the inquiries about Argentina were rather exceptional. In general, they can be grouped into three lines: the analysis of political discourses and gender readings on the scope of the laws about marriage and the grounds for divorce; microhistory studies about the press and letters sent to the government that usually indicates that there was a divorce consensus among the population, although their statements override the possibilities of the sources and type of approach on them; and statistical studies that have made interesting contributions on the national scope, the geographic distribution and the difficulties that the series presents to reflect on other aspects. This work uses a series of data constructed from judicial sources to analyze the social profiles reconstructed in files that in 1955 entered as a divorce to the courts of the city of La Plata (province of Buenos Aires).